2021
DOI: 10.1101/2021.04.06.21254174
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on gastrointestinal infection trends in England, February – July 2020

Abstract: Objective: To establish the impact of the first six months of the COVID-19 outbreak response of gastrointestinal (GI) infection trends in England. Design: Retrospective ecological study using routinely collected national and regional surveillance data from eight Public Health England coordinated laboratory, outbreak and syndromic surveillance systems using key dates of UK governmental policy change to assign phases for comparison between 2020 and historic data. Results: Decreases in GI illness activity wer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…COVID-19 restrictions had a significant effect on the number of cases of gastrointestinal illness (GI) in England and Wales including Cryptosporidium (28), and in this study we have identified that they impacted both C. hominis and C. parvum. anecdotally there were many news stories covering this phenomenon, particularly involving parties and swimming in rivers.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…COVID-19 restrictions had a significant effect on the number of cases of gastrointestinal illness (GI) in England and Wales including Cryptosporidium (28), and in this study we have identified that they impacted both C. hominis and C. parvum. anecdotally there were many news stories covering this phenomenon, particularly involving parties and swimming in rivers.…”
Section: Discussionmentioning
confidence: 76%
“…Most gastrointestinal infections reduced dramatically during the COVID-19 pandemic (37) as childcare and educational settings were closed and eating establishments’ opening hours and social / leisure activities were curtailed. Our hypothesis was that the COVID-19 restrictions might have altered the epidemiology of cryptosporidiosis by infecting species and by time, place and person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By sequence analysis of the gp60 gene, 31/40 (78%) typable C. hominis samples were subtype IbA10G2 which predominates in the UK and much of Europe [ 31 ], but our epidemiological findings may not translate to settings where other subtypes are more prevalent. Since this work was completed, there has been a dramatic change in the epidemiology of Cryptosporidium in the UK with C. parvum becoming the predominant species during the COVID-19 pandemic, following lockdown interventions at the end of March 2020 [ 60 ]. This is currently under investigation by time series analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The number of reported gastrointestinal infection outbreaks in England in the first six months of 2020 was less than half the previous five year average, found a study in BMJ Open 1. Laboratory confirmed infections fell by a third (27 859 cases, against a five year average of 42 495), the researchers found.…”
Section: Covid-19mentioning
confidence: 92%